THE ROLE OF TRADITIONAL LECTURE TO TEACHING MEDICINAL CHEMISTRY IN THE PROFESSIONAL COLLEGE OF BSMU - Велика, Алла; Гарвасюк, Олександра; Кропельницька, Юлія (SWorldJournal, 2024)
Higher education presupposes a successful combination of different forms and methods of teaching. An important role should be assigned to lectures that could enhance the quality of teaching in an educational medium. They are designed to form in students